"I'm Doing Okay": Strengths and Resilience of Children With and Without ADHD. Issue 9 (July 2023) - Charabin, Emma; Climie, Emma A.; Miller, Courtney; Jelinkova, Kristina; Wilkins, Jessica
Background: The body of research directed at understanding the strengths and resilience of this population is growing. Research has indicated there are strengths for individuals with ADHD, and found factors important for promoting good outcomes. This study investigates positive qualities by examining the strengths and resilience of children with and without ADHD. Methods: The final sample included 56 children between the ages of 10 and 17 years (ADHD: n = 38; without ADHD: n = 18). Results: Children in both groups tended to report average levels of strengths and resilience except for school functioning, where significant differences were found between groups. Significant correlations between strengths and resilience for both groups were found. Only family involvement was not significantly correlated with resilience for the without ADHD group. Conclusions: Results from this study emphasize the importance of taking a strength-based perspective when working with children diagnosed with ADHD.